Functional neuroanatomy of gesture–speech integration in children varies with individual differences in gesture processing. Issue 5 (8th March 2018) - Demir‐Lira, Özlem Ece; Asaridou, Salomi S.; Raja Beharelle, Anjali; Holt, Anna E.; Goldin‐Meadow, Susan; Small, Steven L.
Abstract: Gesture is an integral part of children's communicative repertoire. However, little is known about the neurobiology of speech and gesture integration in the developing brain. We investigated how 8‐ to 10‐year‐old children processed gesture that was essential to understanding a set of narratives. We asked whether the functional neuroanatomy of gesture–speech integration varies as a function of (1) the content of speech, and/or (2) individual differences in how gesture is processed. When gestures provided missing information not present in the speech (i.e., disambiguating gesture; e.g., "pet" + flapping palms = bird), the presence of gesture led to increased activity in inferior frontal gyri, the right middle temporal gyrus, and the left superior temporal gyrus, compared to when gesture provided redundant information (i.e., reinforcing gesture; e.g., "bird" + flapping palms = bird). This pattern of activation was found only in children who were able to successfully integrate gesture and speech behaviorally, as indicated by their performance on post‐test story comprehension questions. Children who did not glean meaning from gesture did not show differential activation across the two conditions. Our results suggest that the brain activation pattern for gesture–speech integration in children overlaps with—but is broader than—the pattern in adults performing the same task. Overall, our results provide a possible neurobiological mechanism that could underlie children's increasing ability to integrate gesture and speech over childhood, and account for individual differences in that integration. Abstract : The neural basis of gesture‐speech integration in children varies as a function of the content of the speech and individual differences in how gesture is processed. When gesture disambiguates speech, it leads to increased activity in inferior frontal gyri, the right middle temporal gyrus, and the left superior temporal gyrus, compared to when gesture reinforces speech. Brain activation patterns for gesture‐speech integration are found only in children who display behavioral evidence of being able to glean information from gesture and integrate it with speech.